2001
DOI: 10.1073/pnas.141079498
|View full text |Cite
|
Sign up to set email alerts
|

Hydroperoxide lyase depletion in transgenic potato plants leads to an increase in aphid performance

Abstract: Hydroperoxide lyases (HPLs) catalyze the cleavage of fatty acid hydroperoxides to aldehydes and oxoacids. These volatile aldehydes play a major role in forming the aroma of many plant fruits and flowers. In addition, they have antimicrobial activity in vitro and thus are thought to be involved in the plant defense response against pest and pathogen attack. An HPL activity present in potato leaves has been characterized and shown to cleave specifically 13-hydroperoxides of both linoleic and linolenic acids to y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
189
3
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(208 citation statements)
references
References 30 publications
6
189
3
4
Order By: Relevance
“…Previous work has shown that the relationship between these branches is far beyond that of two similar enzymes competing for the same substrate and suggestive of transcriptional cross-talk between activators of these branched pathways (Halitschke et al, 2004). Initiated with antisense depletion strategies in transgenic potato and tobacco plants that provided the first information on the physiological effects of reducing CYP74B2 expression (Vancanneyt et al, 2001;Halitschke et al, 2004), our discovery of a natural frame-shift deletion in the CYP74B2 locus extends this depletion analysis to analysis of plants completely eliminating functional CYP74B2 activity. We find no evidence for compensation between the HPL and AOS branches of this pathway; when HPL activity is not expressed in the Col ecotype, there is no significant increase in AOS or any of four AOC transcripts needed for synthesis of JA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that the relationship between these branches is far beyond that of two similar enzymes competing for the same substrate and suggestive of transcriptional cross-talk between activators of these branched pathways (Halitschke et al, 2004). Initiated with antisense depletion strategies in transgenic potato and tobacco plants that provided the first information on the physiological effects of reducing CYP74B2 expression (Vancanneyt et al, 2001;Halitschke et al, 2004), our discovery of a natural frame-shift deletion in the CYP74B2 locus extends this depletion analysis to analysis of plants completely eliminating functional CYP74B2 activity. We find no evidence for compensation between the HPL and AOS branches of this pathway; when HPL activity is not expressed in the Col ecotype, there is no significant increase in AOS or any of four AOC transcripts needed for synthesis of JA.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that transcripts from these loci are also induced in herbivoredamaged plants (Reymond et al, 2004) and depleted in the Col ecotype suggests that they also exist downstream of the HPL pathway activated in plant-insect interactions. The immediate effects on insect resistance of inactivating the HPL pathway are complexed by the fact that GLVs have the ability to affect herbivore performance both negatively (by reducing feeding rate, repelling oviposition, or attracting predators; Hildebrand et al, 1993;DeMoraes et al, 2001;Kessler and Baldwin, 2001;Vancanneyt et al, 2001) and positively (by serving as feeding stimulants; Halitschke et al, 2004). Further comparison of the differences in the responses of the Col and Ler ecotypes to herbivore damage will provide more insight into the necessity of having a functional HPL branch in the oxylipin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis thaliana two members of this enzyme family were found, a 13-AOS and a 13-HPL. Moreover, in potato two other isoforms have been described to date, a 9-DES and a 13-HPL Vancanneyt et al, 2001). In order to understand the complex system of CYP74 enzymes and the function of oxylipins in potato, we aimed to identify additional CYP74 enzymes in potato by screening EST databases (www.tigr.org/tdb/lgi).…”
Section: Identification Of New Cyp74 Enzymes In Potatomentioning
confidence: 99%
“…Different C6-volatiles have been shown to induce defence related genes and to stimulate phytoalexin accumulation (Zeringue, 1992;Bate and Rothstein, 1998). In transgenic potato plants lacking HPL transcript an increase in aphid performance was observed (Vancanneyt et al, 2001). Up to now the effect of C9-volatiles has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Colneleic acid is clearly involved in plant defence against pathogens [6,14] and is also an inhibitor of LOX activity [33], but this work is the first indication for a role of colneleic acid during the normal life cycle of the tuber, and for a potential role of colneleic acid in sprout development. It is unlikely that the 9-oxo-nonanoic acid methyl ester in the extracts was formed by the action of HPO lyase on 9-HPOD and HPOT, because it has been demonstrated that potato tuber HPO lyase is specific for 13-HPOD and HPOT [30,34], and the tubers contained little 13-HPOD and HPOT. Moreover, HPO lyase activity rapidly drops to zero during tuber storage [30].…”
Section: Oxylipins During Aging Of Potato Tubersmentioning
confidence: 99%